Audiovisual images and history of the present time (Tempo e Argumento, 2012)
This article written in French was presented as a lecture at the closure of the First International Seminar - History of the Present Time, promoted by the Graduate Program in History of UDESC and ANPUH- Santa Catarina, held on November 7-9, 201, in Florianópolis/SC. It presents discussions about the historians’ interest for the audiovisual media, at the time when this concept, history of the present time, emerges in France.
Keywords: history; audiovisual images; present time